Fluid Models in ihe Traffic Flow Theory - Marušić, Sanja (Promet - Traffic&Transportation, 2012)
This paper presents a survey of results concerning continuum(fluid) models in the the01y of traffic flow. We begin withthe basic LWR model from 1955-56 and describe the benefitsand deficiencies of that model. Ajte1wards we present somenew models developed over the peliod from 1971 (Payne) until1999 (Aw and Rascle) in attempt of correcting the deficienciesof classical L WR model